Experience of the Usage of a Portable X-ray System - Omori, Kazuhiko; Muramatsu, Ken-ichi; Nagasawa, Hiroki; Takeuchi, Ikuto; Kushida, Yoshihiro; Ohsaka, Hiromichi; Jitsuiki, Kei; Oode, Yasumsa; Yanagawa, Youichi (Air Medical Journal, 2020)
The purpose of this study was to introduce the use of a portable X-ray system by the staff members of a doctor helicopter (DH). From January 11 to 18, 2019, we were given temporary access to a portable X-ray system. This period is defined as the investigation term. During the investigation term, a medical chart review was retrospectively performed for all patients who were transported by the DH. We investigated the variables between cases in which an X-ray study had been performed (X-ray group) and had not been performed (control group). Thirteen subjects were classified into the X-ray group, and 17 were classified into the control group. No X-ray studies were performed for patients who underwent interhospital transportation, and the proportion of cases involving patients with exogenous disease in the X-ray group was greater than that in the control group. We reported our experience of DH staff performing X-ray studies at the scene. Further studies are required to determine the indications for using portable X-ray systems in the prehospital setting.